A review of social media use in e-government - Michael J. Magro (Administrative Sciences, 2012)
In the past few years, e-government has been a topic of much interest among those excited about the advent of Web 2.0 technologies. This paper reviews the recent literature concerning Web 2.0, social media, social networking, and how it has been used in the public sector. Key observations include literature themes such as the evolution of social media case studies in the literature, the progress of social media policies and strategies over time, and social media use in disaster management as an important role for government. Other observations include the lack of a tangible goal for e-government, and the idea that significant change is still needed in government culture, philosophy of control, and resource management before broad sustainable success can be achieved in the use of social media.
Keywords: 350; e-government; social media; social networking